2001
DOI: 10.1121/1.1371764
|View full text |Cite
|
Sign up to set email alerts
|

Children’s detection of pure-tone signals with random multitone maskers

Abstract: Preschoolers and adults were asked to detect a 1000-Hz signal, which was masked by a multitone complex. The frequencies and amplitudes of the components in the complex varied randomly and independently on each presentation. A staircase, cued two-interval, forced-choice procedure disguised as a "listening game" was used to obtain signal thresholds in quiet and in the presence of the multitone maskers. The number of components in the masker was fixed within an experimental condition and varied from 2 to 906 acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
101
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(113 citation statements)
references
References 28 publications
9
101
3
Order By: Relevance
“…Neff and Dethlefs (1995) reported masked thresholds spanning a range of 59 dB across 49 adult listeners who, over the course of several studies, participated in similar conditions involving the detection of a 1.0-kHz tone in the presence of random-frequency multitone maskers. Oh et al (2001) noted similar variability among 8 preschool children, reporting informational masking for the preschool children to be on average 20 dB greater than that for 8 adults obtained under identical conditions. Similar adult-child differences have also been reported in the masking effectiveness of a single random-frequency distractor tone (Allen & Wightman, 1995).…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Neff and Dethlefs (1995) reported masked thresholds spanning a range of 59 dB across 49 adult listeners who, over the course of several studies, participated in similar conditions involving the detection of a 1.0-kHz tone in the presence of random-frequency multitone maskers. Oh et al (2001) noted similar variability among 8 preschool children, reporting informational masking for the preschool children to be on average 20 dB greater than that for 8 adults obtained under identical conditions. Similar adult-child differences have also been reported in the masking effectiveness of a single random-frequency distractor tone (Allen & Wightman, 1995).…”
mentioning
confidence: 77%
“…Similar adult-child differences have also been reported in the masking effectiveness of a single random-frequency distractor tone (Allen & Wightman, 1995). The magnitude of these differences can be appreciated by comparing them with findings from traditional tone-in-noise masking studies, where the range of masked thresholds for adults rarely exceeds a few decibels (Patterson, NimmoSmith, Weber, & Milroy, 1982) and where masked thresholds of children are only a few decibels greater on average than those of adults (Oh et al, 2001;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect evidence for this assumption is derived from developmental studies on signal detection in noise. It has been shown that age-related differences in the ability to detect a tone in noise are severely increased when the signal is embedded in an acoustic background that changes randomly on each presentation (Allen & Wightman, 1995;Oh, Wightman, & Lutfi, 2001). This effect has been attributed to age differences in the ability to ignore irrelevant sounds under conditions of uncertainty (Oh et al, 2001(Oh et al, , p. 2893.…”
Section: Discussionmentioning
confidence: 99%
“…This has been found for relatively complex listening tasks, such as speech recognition under challenging listening conditions (e.g., Elliot, 1979;Nábelek and Robinson, 1982) and informational masking (Allen and Wightman, 1995;Hall et al, 2005;Oh et al, 2001;Wightman et al, 2003). It has also been demonstrated for relatively simple tasks, such as the detection of a tone in quiet or in masking noise (Allen and Wightman, 1994;Fior, 1972;Maxon and Hochberg, 1982), frequency discrimination (Jensen and Neff, 1993;Maxon and Hochberg, 1982), and intensity discrimination (Fior, 1972;Maxon and Hochberg, 1982; see also Jensen and Neff, 1993).…”
Section: Introductionmentioning
confidence: 96%